Heat‐precipitation allows the efficient purification of a functional plant‐derived malaria transmission‐blocking vaccine candidate fusion protein. Issue 7 (13th March 2015) - Beiss, Veronique; Spiegel, Holger; Boes, Alexander; Kapelski, Stephanie; Scheuermayer, Matthias; Edgue, Gueven; Sack, Markus; Fendel, Rolf; Reimann, Andreas; Schillberg, Stefan; Pradel, Gabriele; Fischer, Rainer
ABSTRACT Malaria is a vector‐borne disease affecting more than two million people and accounting for more than 600, 000 deaths each year, especially in developing countries. The most serious form of malaria is caused by Plasmodium falciparum. The complex life cycle of this parasite, involving pre‐erythrocytic, asexual and sexual stages, makes vaccine development cumbersome but also offers a broad spectrum of vaccine candidates targeting exactly those stages. Vaccines targeting the sexual stage of P. falciparum are called transmission‐blocking vaccines (TBVs). They do not confer protection for the vaccinated individual but aim to reduce or prevent the transmission of the parasite within a population and are therefore regarded as an essential tool in the fight against the disease. Malaria predominantly affects large populations in developing countries, so TBVs need to be produced in large quantities at low cost. Combining the advantages of eukaryotic expression with a virtually unlimited upscaling potential and a good product safety profile, plant‐based expression systems represent a suitable alternative for the production of TBVs. We report here the high level (300 μg/g fresh leaf weight (FLW)) transient expression in Nicotiana benthamiana leaves of an effective TBV candidate based on a fusion protein F0 comprising Pfs25 and the C0‐domain of Pfs230, and the implementation of a simple and cost‐effective heat treatment step for purification that yields intact recombinant protein at >90% purity with a recovery rate of >70%. The immunization of mice clearly showed that antibodies raised against plant‐derived F0 completely blocked the formation of oocysts in a malaria transmission‐blocking assay (TBA) making F0 an interesting TBV candidate or a component of a multi‐stage malaria vaccine cocktail. Biotechnol. Bioeng. 2015;112: 1297–1305. © 2015 Wiley Periodicals, Inc.